Is There a Scientific Rationale for the Refixation of Delaminated Chondral Flaps in Femoroacetabular Impingement? A Laboratory Study. Issue 4 (April 2020) - Levinson, Clara; Naal, Florian D.; Salzmann, Gian M.; Zenobi-Wong, Marcy; Leunig, Michael
Abstract: Background: Debonding of the acetabular cartilage is a characteristic type of hip damage found in cam-type femoroacetabular impingement (FAI), which remains a treatment challenge. In addition to resection, refixation of these flaps using fibrin sealants has been recently suggested. However, there is only limited evidence available that the proposed refixation method results in sufficient viable cartilage formation to ensure long-term flap grafting and restored tissue function. Questions/purposes: To determine the flap tissue characteristics that would justify refixation of delaminated chondral flaps with a fibrin sealant, we characterized (1) the extracellular matrix (ECM) of chondral flaps in terms of chondrocyte viability and distribution of ECM components and (2) the chondrogenic potential of resident cells to migrate into fibrin and produce a cartilaginous matrix. Methods: Ten acetabular chondral flaps and three non-delaminated control cartilage samples were resected during surgery. Chondrocyte viability was quantified using a live-dead assay. To assess the ECM, histological staining of glycosaminoglycans, collagen II, and collagen I allowed the qualitative study of their distribution. The ability of chondrocytes to migrate out of the ECM was tested by encapsulating minced flap cartilage in fibrin gels and semi-quantitatively assessing the projected area of the gel covered with migrating cells. The potential of chondrocytes to produce a cartilaginous matrix was studied with a pellet assay, a standard three-dimensional culture system to test chondrogenesis. Positive controls were pellets of knee chondrocytes of age-matched donors, which we found in a previous study to have a good capacity to produce cartilage matrix. Statistical significance of controlled quantitative assays was determined by the Student's t-test with Welch's correction. Results: The proportion of viable chondrocytes in flaps was lower than in nondelaminated cartilage (50% ± 19% versus 76 ± 6%; p = 0.02). Histology showed a disrupted ECM in flaps compared with nondelaminated controls, with the presence of fibrillation, a loss of glycosaminoglycan at the delaminated edge, collagen II throughout the whole thickness of the flap, and some collagen I-positive area in two samples. The resident chondrocytes migrated out of this disrupted ECM in all tested samples. However in pellet culture, cells isolated from the flaps showed a qualitatively lower chondrogenic potential compared with positive controls, with a clearly inhomogeneous cell and matrix distribution and an overall smaller projected area (0.4 versus 0.7 mm 2 ; p = 0.038). Conclusion: Despite the presence of viable chondrocytes with migration potential, the cells resided in a structurally altered ECM and had limited capacity to deposit ECM, leading us to question their capacity to produce sufficient ECM within the fibrin sealant for stable long-term attachment of such flaps. Clinical Relevance: The characterization of delaminated cartilage in cam FAI patients suggests that the refixation strategy might be adversely influenced by the low level of ECM produced by the residing cells.